THE PHENOMENON OF UTILIZATION INSTAGRAM AS A PERSONAL BRANDING MEDIUM - Tatia Ridho Ramadhanti; Agus Naryoso, S.Sos, M.Si (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
The widespread of social networking instagram among modern society especially among young people makes social networking instagram very popular today. Instagram popularity cannot be separated form their role as social network that uses the image as a communication tool. Allowing users create their personal galleries. Instagram allows user to show photos and edit it using the features provided in it. Instagram also allows users to do a personal branding through photo they uploaded as wes as through the caption and the hastag which can be added to optimalized the use of SEO (Search Engine Optimizer). This study aimed to describe the individual’s experience in conducting their personal branding instagram through social networking. In this study, the theory used is the dramaturgy of Erving Goffman, supported by interactionism symbolic theory and the theory of personal branding. Experience of this individuals expressed in descriptive qualitative method that focus on invidual’s experience using in-depth interviewed technique to the informant who is an active user of instagram and have been using this social media for more than a year. This study had been done to an individu that has a hobby of photgraphy that has been using instagram for more than a year, had uploaded more than 300 picture and have more than 3000 follower. The result of this study indicate that the social networking instagram user can perform personal branding by presenting their self as good as possible in order or achieve the goal they desired. Instagram is a media that can be used as a medium to communicate its personal branding through photo, caption, hastag, and also comment section. To achieve its objectives of personal branding, the user plays the role of front stage to perform impression management in order to achieve their goal, while at the back stage, users try to maintain things as best as possible so that couldn’t damage their reputation and not to be seen by others and prepare picture, caption and hastag to post as a tool of their personal branding .